Kewenangan Notaris Atas Pembuatan Surat Keterangan Hak Dalam Waris Terhadap Anak Di Luar Nikah - Adhelian Ayu Septyana; Sheha A. Habib; Sulhan S (Jurnal Nuansa Kenotariatan, 2019)
Legal concepts concerning the status of a child born outside marriage with only a civil relationship with the mother and her mother's family experienced a shift in the issuance of the Constitutional Court Decision Number 46/PUU-VIII/2010 concerning the Material Test against Article 2 Paragraph (2) and Article 43 Paragraph (1) Number 1 Year 1974 concerning Marriage. There are 2 (two) issues to be discussed, namely the rights and position of the child outside of marriage after the decision of the Constitutional Court, as well as the authority of Notary in the making of Certificate of Inheritance to the Outer Child after the Constitutional Court Decision. The research method is normative legal research, to obtain the necessary data in connection with the period issues. The result of research is obtained that the decision of the Constitutional Court opens opportunities for the Outer Child to have a civil relationship with father and his father's family as well as the authority of Notary in the making of Certificate of Inheritance to the Outer Child after the Decision of the Constitutional Court Number 46 / PUU-VIII / 2010 becomes very important , It is based on Article 280 of the Civil Code of the civil relationship between the newlyborn child arises when there is already recognition from the mother or his biological father to the child. The deed of recognition shall be made authentically as mandated in Article 281 of the Civil Code. So the government should make regulations relating to children outside of marriage in accordance with the mandate of the Constitutional Court's decision